A Systems Approach to Addressing the Intersection of Mental Health Disability, Homelessness, and the Criminal Justice System. (September 2021) - Vredenburgh, Alexandra N.; Ibrahim, Keyrollos; Bhat-Patel, Priya; Kramer, Jessica
California's economy, alone, is so large that if it were its own country, it would be the 5th largest in the world. Yet, California has an estimated 151, 000 people experiencing homelessness, which is more than any other state in the US. Housing insecurity is often interrelated with mental health and disability and there are several barriers experienced by persons with disabilities, especially when accessing essential needs. There are a multitude of legal barriers that homeless individuals living with disabilities face when seeking government services or interfacing with law enforcement. This panel will discuss how these social challenges intersect, and why a systems approach is needed to address these complicated, interrelated problems.